(untitled) (Revista Archai, 2016)
What kind of weaves do we find in the Platonic dialogues? What its embroideries are meant to show? What type of relations does it maintain with knowledge and its transmission? In this paper I will tackle these questions by analyzing the two passages of Plato’s Phaedrus in which Socrates refers to a veil. I will argue that grasping the function of the veil is needed to correctly understand the meaning of Socrates’s conversing with his interlocutor and the way in which Plato composes the dialogue for his readers. The core aim of this text is to show some key features of Plato’s writings.